Peripus, a new genus of Xanthopygina (Coleoptera: Staphylinidae) from South America - Chatzimanolis, Stylianos; Hightower, Hannah J (Zootaxa, 2019)
We describe a new genus of Xanthopygina as Peripus gen. n. Chatzimanolis & Hightower and include the following species: P. brunkei sp. n. Chatzimanolis & Hightower, P. didontus sp. n. Chatzimanolis & Hightower, P. madrededios sp. n. Chatzimanolis & Hightower, and P. monodontus sp. n. Chatzimanolis & Hightower. Peripus belongs in the Isanopus group of genera of Xanthopygina. We provide photographs, illustrations and a key for the identification of species.